Literatur Review: Pengaruh Rasio Keuangan Dalam Peluang Pengambilan Keputusan Tax Avoidance - Arrahima, Irea (Universitas Muhammadiyah Gresik, 2024)
Tax Avoidance is one of the legal efforts in minimising the tax burden by using loopholes in tax regulations. Financial ratios that can generally affect Tax Avoidance decision making are profitability, leverage and liquidity. This study aims to collect and analyse articles related to the influence of financial ratios in Tax Avoidance. The design used is literature review, articles are collected using a search engine with a focus on national literature published in the 2021-2023 period. Based on the articles collected, the results show that profitability affects the opportunity to make decisions for Tax Avoidance. The increasing profit earned by the entity does not necessarily make the entity will receive an increase in tax burden. In contrast to profitability, leverage and liquidity, which state the entity's ability to meet long-term and short-term obligations, do not always affect the opportunity to make Tax Avoidance decisions.